Radiation Therapy in Early-Stage Invasive Breast Cancer - Lin, Ray (Springer-Verlag, 2011)
The treatment of breast cancer involves a multi-disciplinary approach with radiation therapy playing a key role. Breast-conserving surgery has been an option for women with early-stage breast cancer for over two decades now. Multiple randomized trials now have demonstrated the efficacy of breast-conserving surgery followed by radiation therapy. With the advancements in breast imaging and the successful campaign for early detection of breast cancer, more women today are found to have early-stage small breast cancers. Patient factors (breast size, tumor location, history of prior radiation therapy, preexisting conditions such as collagen vascular disease, age, having prosthetically augmented breasts), pathological factors (margin status, tumor size, presence of extensive intraductal component requiring multiple surgical excisions), as well as patient preference are all taken into consideration prior to surgical management of breast cancer. Whole-breast fractionated radiation therapy between 5 and 7 weeks is considered as the standard of care treatment following breast-conserving surgery. However, new radiation treatment strategies have been developed in recent years to provide alternatives to the conventional 5–7 week whole-breast radiation therapy for some patients. Accelerated partial breast radiation therapy (APBI) was introduced because the frequency of breast recurrences outside of the surgical cavity has been shown to be low. This technique allows treatments to be delivered quicker (usually 1 week, twice daily) to a limited volume. Often times, this treatment involves the use of a brachytherapy applicator to be placed into the surgical cavity following breast-conserving surgery. Accelerated hypofractionated whole-breast irradiation may be another faster way to deliver radiation therapy following breast-conserving surgery. This journal article reviews the role of radiation therapy in women with early-stage breast cancer addressing patient selection in breast-conserving therapy, a review of pertinent trials in breast-conserving therapy, as well as the different treatment techniques available to women following breast-conserving surgery.